Lessons learned? South Korea's foreign policy toward North Korea under the Moon Jae-in administration - Hannes B. Mosler (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2022)
What are the characteristics of President Moon Jae-in's policy toward North Korea, and what lessons can be drawn for the future? More than 70 years have passed since the establishment of the two republics in 1948, during which continuous attempts have been made to achieve reconciliation, peace, and prosperity on the Korean peninsula. Even though the Korean War (1950-53) as well as the last authoritarian government in South Korea (until 1987) belong to the ever more distant past, neither, obviously, have the conflicts between the two Koreas ceased, nor has South Korea found a reasonable and effective way of addressing the conundrum. Against this backdrop of more than half a century of contentious inter-Korean relations, the paper examines the foreign policy (efforts) by the Moon administration (2017-2022) toward North Korea in order to shed light on challenges and opportunities for the future regarding the region of East Asia as well as inter-regional policy implications.
Keywords: 330; Moon Jae-in; North Korea; South Korea; foreign policy; two-level game; USA; EU; Korean Peninsula Policy; Eurasia